Factors influencing pediatric nurses' perception, knowledge and attitude towards suspecting and reporting child abuse in HUSM - Kuppusamy, Grete (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
Pediatric nurses plays a very important role in suspecting and reporting child abuse cases in pediatric wards. Personal attributes such as age, nursing education level, marital status, years of working experience and child abuse training course experience will be the factors that influences nurses perception, knowledge and attitudes towards suspecting and reporting child abuse cases. Thus this crosssectional study was conducted to examine the association between personal attributes of nurses with their perception, knowledge and attitudes towards child abuse. This study questionnaire consists of 11 demographic characteristic questions and 35 Likert-type questionnaires. The questionnaire for this study compromised of four parts which is the purpose to measure pediatric nurses' perceptions, knowledge and attitude towards child abuse and neglect. The data for this study was collected by using self-administered questionnaire. Targeted group were pediatric nurses working in all pediatric wards in HUSM. Fourty-eight pediatric nurses voluntarily become participants for this study. Statistical analysis carried out using SPSS version 18.0 and data were analyzed by descriptive statistics, independent t-test and one way ANOVA. Results shows that there were only association between education level (p=0.007) and years of working experience (p=0.01 0) with pediatric nurses perception (p<0.05). There were also 2 factors that influenced the attitudes of nurses which were, education level (p=0.030) and the experience of attending child abuse training (p=0.031 ), (p<0.05). Whereas, there were no association between all factors with nurses' knowledge towards suspecting and reporting (p>0.05). xi